Diálogos del arte y la arquitectura a través de la revista ’Arquitectura’ (1959-1973) - Bernal, Amparo (Arte, Individuo y Sociedad, 2020)
This article analyzes the role of the magazine Arquitectura in the dissemination of art and in the creation of an environment to contribute to the interdisciplinary dialogue between architects and artists. The fifteen years of this editorial stage, between 1959 and 1973, mainly coincide with a period of international openness of the Franco regime dictatorship and unprecedented development in the Spanish economy, which favored the an extraordinary demand in all fields of architecture. As a consequence of the permeability of our borders, Spanish art began to be recognized abroad, and in turn, our artists, photographers, and graphic designers became imbued with the artistic currents that came from outside. All these expressions of art were reflected in the graphic image and content of the magazine with the aim of reflecting the artistic and cultural context in which the architecture was integrated. For this reason, Arquitectura was not only a printed medium but as the media of the College of Architects of Madrid, it also generated an intellectual and cultural environment that benefited connections of architecture with art and artists, creating an open space for all artistic expression form.